TEACHING STRATEGY ON SPEAKING ABILITY FOR ELEVENTH GRADE AT SMA RK SERDANG MURNI LUBUK PAKAM - Ranto Nicolius Turnip; Masitowarni Siregar; Rahmad Husein (GENRE JOURNAL : Journal of Applied Linguistics of FBS Unimed, 2020)
This study aimed to find out the strategy on teaching English on Speaking skill which is implemented in SMA RK Serdang Murni Lubuk Pakam. The research was conducted by using descriptive qualitative analysis. It was conducted in SMA RK Serdang Murni Lubuk Pakam, especially the English teacher who taught for the eleventh grade students at SMA RK Serdang Murni Lubuk Pakam. The data were gathered by administering interview and classroom observation. From the result of the analysis, it was found that the teacher used practicing dialogue and discussion as the strategy to teach the eleventh-grade students at SMA RK Serdang Murni Lubuk Pakam. The strategy wasn’t going according to lesson plan goal. It was caused several things, such as; the teacher ran the class activity monotonously, there were less speaking activities in the class, the students didn’t have intention to be involved in class activity, and the students’ willingness was also low. Therefore the researcher believes that the teaching strategy by using discussions and practicing dialogue were not effective in teaching and learning process for the eleventh grade students at SMA RK Serdang Murni Lubuk Pakam.